Analysis of Factors Affecting Islamic Financial Literacy among Students (Case Study of Islamic Banking Students of UIN North Sumatra) - Siregar, Nabila Safutri; Nasution, Juliana; Inayah, Nurul (Li Falah: Journal of Islamic Economics and Business, 2025)
The purpose of this study is to investigate how gender influences (X1) and financial knowledge (X2) on Islamic financial literacy (Y) among students of the Islamic Banking Study Program at UINSU. The research employs a quantitative method utilizing data gathered from 91 respondents as well as examination of multiple linear regression.  The findings indicate that gender significantly influences Islamic financial literacy, with male students demonstrating higher literacy levels compared to females. Financial knowledge also has a significant impact and serves as the dominant factor in enhancing Islamic financial literacy. Simultaneously, both X1 and X2 variables significantly impact Islamic financial literacy, contributing more than fifty percent. This research was conducted to have a positive impact on students, especially the UINSU Islamic Banking Study Program, in increasing finansial knowledge related to Islamic financial principles and practices.